2005
DOI: 10.1080/00074910500072732
|View full text |Cite
|
Sign up to set email alerts
|

How many Chinese Indonesians?

Abstract: Until the census of 2000, no attempt had been made since the 1930 census to elicit data from Indonesians about their ethnicity. The 2000 census question on the subject was necessarily based on self-identification. However, the very low figure recorded for ethnic Chinese Indonesians implies that large numbers of them chose not to identify themselves as such, probably because of fears aroused by outbreaks of anti-Chinese violence in 1998. The 2000 census figure of only 1.8 million Chinese, less than 1% of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Some Chinese Indonesians hesitate to reveal their ethnic identity due to fears of stigmatization and discrimination, and thus it might be hard to obtain their demographic information [10]. However, a comprehensive study from 2016 revealed that there are around 1.2% of Chinese Indonesians residing in the country, contrary to other sources that mention in the 3%-3.3% range [11][12][13][14][15][16]. See also [17][18][19][20][21][22] for a well-rounded perspective on Chinese Indonesians.…”
Section: Ethnic Groups In Javamentioning
confidence: 99%
“…Some Chinese Indonesians hesitate to reveal their ethnic identity due to fears of stigmatization and discrimination, and thus it might be hard to obtain their demographic information [10]. However, a comprehensive study from 2016 revealed that there are around 1.2% of Chinese Indonesians residing in the country, contrary to other sources that mention in the 3%-3.3% range [11][12][13][14][15][16]. See also [17][18][19][20][21][22] for a well-rounded perspective on Chinese Indonesians.…”
Section: Ethnic Groups In Javamentioning
confidence: 99%
“…Accordingly, we respond to this gap by researching Chinese Indonesians, an ethnic minority group in Indonesia that encompasses around 3% of the national population or approximately equal to seven million people (Arifin et al, 2017;Mackie, 2005;Rakhmat, 2021). Additionally, Indonesia has the most Chinese of all the countries in the world (more than eight million), which represents around 17% of all overseas Chinese (Poston & Zhang, 2021).…”
Section: The Prevalence and Associated Factors For Self-harm And Suic...mentioning
confidence: 99%
“…Prosesi silang budaya tidak hanya mengarahkan perhatian pada produk paduan budaya, melainkan penempatan posisi produk dalam ruang sosial-historis di bawah pemaksaan dan penolakan pada kekuasaan (Foulcher dan Day, 2008 (Hoon, 2006b(Hoon, , 2006aSuryadinata, 1978;. (Lindblad, 2007;Mackie, 2005). "masih ada mungkin yang membedakan, tapi kita sama orang Jawa, juga gak boleh berbeda sikap, kita sama-sama orang Lasem, makanya kita harus bersatu, gak ada Cina, gak ada Jawa disini, semuanya sama, saling rukun, menghormati" (Wawancara dengan PW, 2019)…”
Section: Hibridasi Dan Mimikriunclassified